High-solubility salts of the multiple sclerosis drug teriflunomide - Gunnam, Anilkumar; Nangia, Ashwini K. (Crystal Growth & Design, 2019)
Teriflunomide (TFM) is an immunomodulatory prodrug of leflunomide which is used for the treatment of multiple sclerosis (MS). It is a Biopharmaceutics Classification System Class (BCS) II drug with low solubility and high permeability. The X-ray crystal structure of TFM is stabilized by O-H center dot center dot center dot O, C-H center dot center dot center dot O, C-H center dot center dot center dot N, and N-H center dot center dot center dot N interactions. In order to study the solubility and dissolution changes of this drug, five multicomponent crystal forms were prepared with amine and amide generally regarded as safe (GRAS) coformers to improve the physicochemical properties such as solubility, dissolution, diffusion, and phase stability. Equimolar TFM-coformer 1:1 salts were crystallized, except for cytosine which afforded a salt cocrystal toluene solvate TFM-CYT-TOL in a 1:2:1 ratio. The multicomponent forms were crystallized by slow solvent evaporation and characterized by single crystal X-ray diffraction. TFM and coformer are bonded by N+-H center dot center dot center dot O-, N-H center dot center dot center dot O, O-H center dot center dot center dot O, C-H center dot center dot center dot O, C-H center dot center dot center dot N, N-H center dot center dot center dot N, and C-H center dot center dot center dot F interactions. The bulk phase purity of the salts was characterized by powder X-ray diffraction and infrared and thermal techniques. Solubility, dissolution, and diffusion experiments in pH 7.0 buffer exhibited a significant improvement compared to the reference drug. The morphology and particle size of salts by field emission scanning electron microscopy were related to dissolution behavior. The highest solubility, dissolution, and diffusion profile were observed for TFM-MEA and TFM-TEA salts (monoethanol amine and triethanol amine).